2016
DOI: 10.7717/peerj.1814
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiles during short-term heat stress; branchingvs.massive Scleractinian corals of the Red Sea

Abstract: It is well-established that there is a hierarchy of susceptibilities amongst coral genera during heat-stress. However, molecular mechanisms governing these differences are still poorly understood. Here we explored if specific corals possessing different morphologies and different susceptibilities to heat stress may manifest varied gene expression patterns. We examined expression patterns of seven genes in the branching corals Stylophora pistillata and Acropora eurystoma and additionally in the massive robust c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 89 publications
(131 reference statements)
4
29
0
Order By: Relevance
“…Besides, the differential expression of lectins and components of the complement system and the cytoskeleton suggests that the environmental stress response in corals and oysters may be similar. Concerning the CSR, our results are also consistent with previous studies investigating the coral response to elevated seawater temperatures, showing heat shock, unfolded protein and oxidative stress responses as well as decreased ribosome biogenesis (Bay & Palumbi, , ; Bellantuono, Granados‐Cifuentes, Miller, Hoegh‐Guldberg, & Rodriguez‐Lanetty, ; Maor‐Landaw & Levy, ; Maor‐Landaw et al., ; Meyer et al., ; Rodriguez‐Lanetty et al., ; Vidal‐Dupiol et al., ; Voolstra et al., ).…”
Section: Discussionsupporting
confidence: 91%
“…Besides, the differential expression of lectins and components of the complement system and the cytoskeleton suggests that the environmental stress response in corals and oysters may be similar. Concerning the CSR, our results are also consistent with previous studies investigating the coral response to elevated seawater temperatures, showing heat shock, unfolded protein and oxidative stress responses as well as decreased ribosome biogenesis (Bay & Palumbi, , ; Bellantuono, Granados‐Cifuentes, Miller, Hoegh‐Guldberg, & Rodriguez‐Lanetty, ; Maor‐Landaw & Levy, ; Maor‐Landaw et al., ; Meyer et al., ; Rodriguez‐Lanetty et al., ; Vidal‐Dupiol et al., ; Voolstra et al., ).…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, the coral S. pistillata in our study is an exception to the linear relationship between [1 -C] utilization and thermal tolerance in spring, and despite utilizing preferential [1 -C] at similar levels to M. digitata and P. lutea, photochemical efficiency collapsed entirely for this species in response to transient heat stress. In other regions such as the Red Sea, S. pistillata exhibits robust host-specific responses to temperature stress and are considered thermally tolerant (Maor-Landaw et al, 2014;Maor-Landaw and Levy, 2016). However, the overall sensitive nature of the S. pistillataSymbiodinium symbioses at Heron Reef is well-documented (Table 1) and the host seems to be inherently less prepared to cope with transient heat stress than other species in this study (comparatively low mucus production, antioxidant enzyme function, and heat-shock protein content; Fitt et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst anomalous temperatures appear to target numerous physiological pathways of both the coral host and their Symbiodinium populations (Baird et al, 2009;Maor-Landaw and Levy, 2016), functional impairment of Symbiodinium's photosystem II (PSII) reaction centers (RCII) often responds as a primary determinant of bleaching-stress susceptibility (Warner et al, 1999;Takahashi et al, 2008). PSII utilizes absorbed light energy to drive electron generation for energy (ATP) and reductant (NADPH) formation, supporting carbon fixation (Oakley et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Omics methods were previously only utilized in a handful of studies, but are currently one of the most common tools applied in the field (Figure 1) and thus the primary focus of the following sections. Barshis et al, 2013;DeSalvo, Sunagawa, Fisher, et al, 2010;Fitt et al, 2009;Kenkel, Meyer, & Matz, 2013;Maor-Landaw & Levy, 2016) (Figure 2). These response patterns are not only limited to adult colonies, but heat stress studies on larvae and larval development have also shown similar cellular responses (Negri, Marshall, & Heyward, 2007;Polato et al, 2010;Portune, Voolstra, Medina, & Szmant, 2010;Rodriguez-Lanetty, Harii, & Hoegh-Guldberg, 2009;Voolstra et al, 2009).…”
Section: The Rise Of Transcriptomicsmentioning
confidence: 99%
“…Temperature-stressed cnidarians experienced (a) increased HSP expression, (b) increased antioxidant expression, (c) decreased Ca 2+ homeostasis, (d) restructured ECM, (e) rearrangement of actin cytoskeleton, (f) decreased ribosomal protein expression, and (g) pro-apoptotic responses (Abrego, Ulstrup, Willis, Van, & Oppen, 2008;Barshis et al, 2013;DeSalvo, Sunagawa, Fisher, et al, 2010;Fitt et al, 2009;Kenkel, Meyer, & Matz, 2013;Maor-Landaw & Levy, 2016) (Figure 2). Studies on important reef-building species, such as O. faveolata (DeSalvo et al, 2008) and Acropora palmata (DeSalvo, Sunagawa, Voolstra, & Medina, 2010), have revealed an assortment of crucial heat stress genes in cnidarians, such as peroxidasin, C/EBP, EF-hand, and calmodulin.…”
mentioning
confidence: 99%